Perceptions and practices regarding menstruation in adolescent girls in Yazd - Karbasi, Sedighah Akhavan; Golestan, Motahharen; Fallah, Razieh (Nepal Journal of Obstetrics and Gynaecology, 2014)
Objective: Puberty is the most prominent stage of life. The purpose of this study was to evaluate effects of puberty health education on promoting of its awareness in girls. Methods: In an interventional quasi-experimental study (pre and post test), awareness, attitude and practice of 500 high school first grade student girls evaluated before and after health education in Yazd in 2004- 2005 . Results: Mean age of menarche was 13.46±1.12. Over ninty three percent (93.6%) of girls had a previous information about menstruation where mother was the major source (53%). Good and poor knowledge were seen in 36% and 28.6% respectively but practice was seen in 24.4% and 32.8% respectively. 85.2% of girls believed that menarche is evidence of health, but in 91.6% girl’s menarche was associated with worry and shame. Negative psychological attitude about menstruation was seen in 59.8%. The mean number of knowledge and practice before and after intervention was 5.3±2.9, 11.8±2.18 and 4.3± 1.8 and 10.2 ± 2.3 respectively (PV =0.0001). Conclusion: Educational programs are needed for girls and their mothers to correct misinformation about exercise, food restrictions and good health puberty and menarche. DOI: http://dx.doi.org/10.3126/njog.v3i2.10830 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 40-43